PROBLEMS OF FOREIGN LANGUAGE TEACHING - Shohida Isakova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
in the article, one of the important aspects of modern science and education, that is, learning foreign languages ​​is more relevant than ever, learning foreign languages ​​in the era of information, communication and high technologies, knowing foreign languages ​​is one of the most important aspects of a modern, intelligent person, foreign language, especially the problems of teaching a second foreign language are highlighted. It contains the main problems faced by the teacher and students during foreign language teaching to the students of the specialist or non-specialist faculty.